Unconventional monetary policy in the Euro zone - Driffill, John (2016)
The European Central Bank adopted a policy of quantitative easing early in 2015, long after the US and UK, and after implementing a succession of measures to increase liquidity in the Euro zone financial markets, none of which proved sufficient eventually. The paper draws out lessons for the Euro zone from US and UK experience. Numerous event studies have been undertaken to uncover the effects of QE on yields on and prices of financial assets. Estimated effects on long-term government bond yields are then converted into the size of the cut in the policy rate that would normally have been needed to produce them. From these implicit cuts in policy rates, estimates of the effect on GDP and inflation are generated. Euro zone QE appears to have had a much smaller effect on bond yields for the core members states than did QE in the US or UK. Therefore its effects on output and inflation are likely to be proportionately smaller. Its effects on long-term government bond yields in periphery members are greater. QE is compressing interest differential among Euro zone member states. The dangers of QE to which various commentators draw attention, that it creates a danger of inflation in the future, that it creates asset price bubbles, that it allows zombie firms and banks to survive, slowing down the process of adjustment, seem remote. Meanwhile it makes a useful contribution to cutting the costs of debt service and allowing member states more fiscal room for maneouvre.